Age and Ageing to introduce a new category of paper: healthcare improvement science. (5th November 2018) - Parker, S G; Downes, T; Godfrey, M; Matthews, R; Martin, F C
Abstract: Age and Ageing is now inviting papers on healthcare improvement for older people. In this article we outline the nature and scope of healthcare improvement and reference improvement models and the tools and methods of improvement science. We emphasise the issues of sustainability, including scale and spread; evaluation – including associated ethical consideration and the involvement of patients and the public in healthcare improvement and associated research. Throughout we refer to resources the authors have found useful in their own work, and provide a bibliography of sources and web-links which will provide essential guidance and support for potential contributors to this new category of submission to Age and Ageing.